Pembentukan Keterampilan Tambahan pada igenerasi Melalui Pelatihan Desain Komunikasi Visual - Zuhri, Al; Manurung, Lora Regina; Putri Pelangi; Riza Kania; Riska; M. Iqbal; Hasibuan, Syahir Afwan; Sariana (Fakultas Pertanian, Universitas Samudra, 2024)
The ability and creativity to create visual designs is very necessary in the current technological era. In fact, it is really needed in the world of work, such as in the fields of printing, advertising, multimedia, fashion and other creative industries. However, not all schools can facilitate tools and training to support students in designing as an effort to develop additional skills. So the aim of this service is to improve students' additional skills in graphic design with the sample being practiced is making a certificate using the professional application, Adobe Photoshop. The subjects in this activity were class X students, Department of Computer Network Engineering (TKJ), SMK Negeri 1 Meulaboh with 20 students involved. Socialization regarding this design is carried out using education, discussion and demonstration methods (direct practice). The final result achieved was that the students' understanding and ability to operate Photoshop and how to create certificates experienced a significant increase, this can be seen from the start of the activity to the production of four certificate designs as the final output of the activity.